Pentingnya Pengetahuan Pemeriksaan Payudara Sendiri sebagai Deteksi Dini Kanker Payudara - Supriyatiningsih, Supriyatiningsih; Rachmanio, Nicko; Kurniawan, Muhammad (Berdikari: Jurnal Inovasi dan Penerapan Ipteks, 2022)
Breast cancer is included in the five types of cancer that result in death. The reason is the delay in early detection so that survivors of this type of cancer are generally detected at an advanced stage. The community service entitled "PKM Knowledge and Early Detection of Breast Cancer in Women of Reproductive Age" aims to provide knowledge about the importance of breast self-examination (BSE) as an effort to detect breast cancer early. The method used is through online seminars via Zoom Meetings to 20 employees and their families at the Obstetrics and Gynecology Clinic, Muhammadiyah Asri Medical Center Hospital, Yogyakarta. The material provided was in the form of knowledge about women's health, breast cancer and its treatment, and training on BSE, which was preceded by a pretest to measure participants' knowledge before the seminar and a posttest at the end of the activity after receiving the seminar. The results of the pretest and posttest were analyzed using the Wilcoxon Signed-Rank test method. The results of the pretest showed that 17 participants (85.0%) had sufficient knowledge about BSE and 2 participants (10.0%) had less knowledge. The posttest results showed that all participants (100.0%) had knowledge in the good category about BSE. The test results showed a significance value of 0.001 (p 0.05), which means that there was a significant increase in participants' knowledge about BSE as early detection of breast cancer before and after the seminar.